Acceptability measures of water, sanitation and hygiene interventions in low- and middle-income countries, a systematic review. - Rose Hosking; Suji Y O'Connor; Kinley Wangdi; Johanna Kurscheid; Aparna Lal (Public Library of Science (PLoS), 2022)
Background Inadequate access to water, sanitation, and hygiene (WASH) is an environmental risk factor for poor health outcomes globally, particularly for children in low- and middle-income countries (LMIC). Despite technological advancements, many interventions aimed at improving WASH access return less than optimal results on long term impact, efficacy and sustainability. Research focus in the 'WASH sector' has recently expanded from investigating 'which interventions work' to 'how they are best implemented'. The 'acceptability' of an intervention is a key component of implementation that can influence initial uptake and sustained use. Acceptability assessments are increasingly common for health interventions in clinical settings. A broad scale assessment of how acceptability has been measured in the WASH sector, however, has not yet been conducted. Methods/principal findings We conducted a systematic literature review of intervention studies published between 1990 and 2021 that evaluated the acceptability of WASH interventions in LMIC settings. Using an implementation science approach, focused outcomes included how acceptability was measured and defined, and the timing of acceptability assessment. We conducted quality assessment for all included studies using the Cochrane Risk of Bias tool for randomised studies, and the Newcastle-Ottawa Scale for non-randomised studies. Of the 1238 records; 36 studies were included for the analysis, 22 of which were non-randomized interventions and 16 randomized or cluster-randomized trials. We found that among the 36 studies, four explicitly defined their acceptability measure, and six used a behavioural framework to inform their acceptability study design. There were few acceptability evaluations in schools and healthcare facilities. While all studies reported measuring WASH acceptability, the measures were often not comparable or described. Conclusions As focus in WASH research shifts towards implementation, a consistent approach to including, defining, and measuring acceptability is needed.